ML-23 The outcome of malignant lymphoma of the central nervous system in a single institution. (28th November 2020) - Kuwahara, Kiyonori; Ohba, Shigeo; Matsumura, Kazuyasu; Higashiguchi, Saeko; Kojima, Daijiro; Muto, Jun; Nakae, Shunsuke; Nishiyama, Yuya; Yamada, Seiji; Adachi, Kazuhide; Abe, Masato; Hasegawa, Mitsuhiro; et al.
Abstract: Background: Although high dose-methotrexate therapy has been performed for primary central nervous system malignant lymphoma (PCNSL), R-MPV (rituximab, methotrexate (MTX), procarbazine and vincristine) therapy is currently the first line therapy for (PCNSL) in our hospital. This study examines the results of R-MPV therapy comparing with past treatment. Method/Subjects: Thirty-seven patients treated at our hospital from 2009 to 2020 were included. Overall survival time, progression free survival time, and toxicities were evaluated. Results: The average age of patients was 65.7 years. Patients included 21 males and 16 females. Thirty-six patients were diagnosed DLBCL by resected brain tumor tissues, and one was diagnosed DLBCL by vitreous biopsy. As initial treatment, rituximab±HD-MTX therapy (R±MTX group) was performed in 20 cases, HD-MTX therapy plus radiation (R±MTX+RT group) was performed in 12 cases, and RMPV therapy was performed in 5 cases (R-MPV group). Median OS of all cases was 69 months and median PFS was 38 months. Median OS was 69 months in R±MTX group and could not be calculated in R±MTX+RT, and R-MPV groups. Median PFS was 16 months and 56 months in R±MTX group and R±MTX+RT, respectively, and could not be calculated in the R-MPV group. Although the R-MPV group had a short follow-up period, the results were considered to be comparable to those of the R±MTX+RT group. On the other hand, grade 3/4 adverse events occurred in 50%, 25%, and 100%, respectively. Conclusion: R-MPV therapy may delay the timing of radiation and reduce the amount of radiation. On the other hand, the frequency of adverse events is high, and more strict management of treatment is required.